Caminhos para uma hermenêutica jurídica aplicável às empresas transnacionais - Vailatti, Diogo Basilio (2020)
This research will make an analysis of Transnational Companies and business ethics within a model of construction of the legal norm, seeking to outline a proper model of hermeneutics applicable to such a business model. In this sense, starting from the idea that there are both gaps and textual excesses related to the rules and principles applicable to Transnational Companies, the work will verify what are the sources and criteria that can be used in such cases. Therefore, the research will be divided into three chapters. The first chapter will analyze the public system of corporate regulation. The second chapter will focus on the private system of business self-regulation. The third and last chapter will look at how the public and private systems are used in conjunction with ethics for the construction of the legal standard related to the transnational business sector, in order to verify the hermeneutics specific model in such segment. The research is part of the research line “Ethics, Language and Law”, focusing on the Philosophy of Law. As for research techniques, the work uses bibliographic and documentary analysis. Regarding the methods, the work uses the hypothetical-deductive method